2003
DOI: 10.1016/s0304-3835(02)00718-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of overexpressed connective tissue growth factor on tumor cell growth in a human oral squamous cell carcinoma-derived cell line

Abstract: Connective tissue growth factor (CTGF) is known to be a multifunctional growth factor that is overexpressed in several types of malignancies. In this study, effects of CTGF gene overexpression on the phenotypes of oral squamous cell carcinoma cells were investigated by using a cell line with undetectable endogenous CTGF expression. Surprisingly, our results indicated that CTGF-overexpressed clones were characterized by attenuated cell growth and less potent tumorigenicity, with coincidental downregulation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Although CTGF was found to be overexpressed in oesophageal carcinoma (Koliopanos et al 2002), highest levels were associated with longer survival in squamous cell carcinoma, but with shorter survival in adenocarcinoma. In squamous cell carcinoma of the oesophagus, high levels of CTGF are associated with longer survival (Koliopanos et al 2002), and overexpression of CTGF in oral squamous cell carcinoma is associated with slower growth (Moritani et al 2003). In breast cancer, CTGF has been found to be associated with nodal status and tumour size (Xie et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CTGF was found to be overexpressed in oesophageal carcinoma (Koliopanos et al 2002), highest levels were associated with longer survival in squamous cell carcinoma, but with shorter survival in adenocarcinoma. In squamous cell carcinoma of the oesophagus, high levels of CTGF are associated with longer survival (Koliopanos et al 2002), and overexpression of CTGF in oral squamous cell carcinoma is associated with slower growth (Moritani et al 2003). In breast cancer, CTGF has been found to be associated with nodal status and tumour size (Xie et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of MCF-7 with CTGF expression vector results in a high degree of apoptosis (Hishikawa et al 1999). This has been supported partly by a recent study which shows that over-expression of CTGF in oral squamous cell carcinoma results in reduction in cell growth and tumorigenesis (Moritani et al 2003). Nov/CCN3 is probably the least-studied CCN member.…”
Section: Introductionmentioning
confidence: 90%
“…26,27 In contrast, several other studies have reported a relation between the overexpression of CTGF and cancer inhibition. 28,29 Interestingly, CTGF induces apoptosis in MCF-7 cells and aortic smooth muscle cells. 30,31 A recent study suggested that loss of CRYAB expression might be involved in promoting ovarian tumorigenesis or tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CTGF levels have been detected in a number of cancers including pancreatic (15), breast (16), glioblastoma (17,18), esophageal (19), melanoma (20), chondrosarcoma (21), oral squamous cell cancer (22), acute lymphoblastic leukemia (23), rhabdomyosarcoma (24), and hepatocellular carcinoma (25), but its direct role in tumor suppression or progression has not been investigated in pancreatic cancer nor with therapeutic agents with the capacity to inhibit CTGF function in vivo. An increase in CTGF was reported to be associated with decreased survival of patients with breast cancer (16), glioblastoma (18), or adenocarcinoma of the esophagus (19), and increased breast cancer bone metastasis in a mouse model (26).…”
Section: Introductionmentioning
confidence: 99%